2022
DOI: 10.1039/d2cc04892b
|View full text |Cite
|
Sign up to set email alerts
|

Silylium ion-mediated cage-opening functionalization of closo-B10H102− salts

Abstract: The cage-opening functionalization of stable closo-B10H102- salts constitutes a great way to get various boron clusters. However, the known methods to mediate cage-opening functionalization rely on the use of strong...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The reaction of decaborane (14) The reactions of Na 2 [closo-B 10 H 10 ] with thiols RSH (R = i-Pr, i-Bu, c-Hx, C 6 H 4 -p-Me, C 6 H 4 -p-F) in hexane in the presence of trimethylsilyl triflate led to the corresponding 6alkyl-and 6-arylsulfides [6-RS-B 10 H 13 ] [205]. It should be noted that the direct reactions of decaborane (14) with alkyl thiols RS lead to its complete degradation to the corresponding trialkylthioborates (RS) 3 B [220].…”
Section: Derivatives With a B-s Bondmentioning
confidence: 99%
“…The reaction of decaborane (14) The reactions of Na 2 [closo-B 10 H 10 ] with thiols RSH (R = i-Pr, i-Bu, c-Hx, C 6 H 4 -p-Me, C 6 H 4 -p-F) in hexane in the presence of trimethylsilyl triflate led to the corresponding 6alkyl-and 6-arylsulfides [6-RS-B 10 H 13 ] [205]. It should be noted that the direct reactions of decaborane (14) with alkyl thiols RS lead to its complete degradation to the corresponding trialkylthioborates (RS) 3 B [220].…”
Section: Derivatives With a B-s Bondmentioning
confidence: 99%
“…Due to these characteristics, they could be potentially utilized as good hydrohalogenation reagents with good selectivity under mild conditions. 38,39 Herein, we wish to show that with the proper choice of Lewis acids, TMSX (X = Br, Cl) could be employed as efficient hydrobromination and hydrochlorination reagents of terminal alkynes with excellent regioselectivity at room temperature (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, we found that TMSOTf could activate the stable closo-B 12 H 12 2− salt and afforded the ring-opening functionalized product in the presence of nucleophiles (alcohol, thiol). 15 Preliminary mechanistic studies indicated that TMSOTf worked similarly with HOTf, yet with a broader substrate scope due to its milder Lewis acidity. So, we assume that other TMSX reagents could be explored in the classical HX-involved reactions with the help of a catalyst.…”
mentioning
confidence: 99%
“…Our group has a special interest in organosilicon chemistry. In 2022, we found that TMSOTf could activate the stable closo -B 12 H 12 2– salt and afforded the ring-opening functionalized product in the presence of nucleophiles (alcohol, thiol) . Preliminary mechanistic studies indicated that TMSOTf worked similarly with HOTf, yet with a broader substrate scope due to its milder Lewis acidity.…”
mentioning
confidence: 99%